An Integrative Model for Soil Biogeochemistry and Methane Processes: I. Model Structure and Sensitivity Analysis. Issue 8 (10th August 2021) - Ricciuto, Daniel M.; Xu, Xiaofeng; Shi, Xiaoying; Wang, Yihui; Song, Xia; Schadt, Christopher W.; Griffiths, Natalie A.; Mao, Jiafu; Warren, Jeffrey M.; Thornton, Peter E.; Chanton, Jeff; Keller, Jason K.; et al.
Abstract: Environmental changes are anticipated to generate substantial impacts on carbon cycling in peatlands, affecting terrestrial‐climate feedbacks. Understanding how peatland methane (CH4 ) fluxes respond to these changing environments is critical for predicting the magnitude of feedbacks from peatlands to global climate change. To improve predictions of CH4 fluxes in response to changes such as elevated atmospheric CO2 concentrations and warming, it is essential for Earth system models to include increased realism to simulate CH4 processes in a more mechanistic way. To address this need, we incorporated a new microbial‐functional group‐based CH4 module into the Energy Exascale Earth System land model (ELM) and tested it with multiple observational data sets at an ombrotrophic peatland bog in northern Minnesota. The model is able to simulate observed land surface CH4 fluxes and fundamental mechanisms contributing to these throughout the soil profile. The model reproduced the observed vertical distributions of dissolved organic carbon and acetate concentrations. The seasonality of acetoclastic and hydrogenotrophic methanogenesis—two key processes for CH4 production—and CH4 concentration along the soil profile were accurately simulated. Meanwhile, the model estimated that plant‐mediated transport, diffusion, and ebullition contributed to ∼23.5%, 15.0%, and 61.5% of CH4 transport, respectively. A parameter sensitivity analysis showed that CH4 substrate and CH4 production were the most critical mechanisms regulating temporal patterns of surface CH4 fluxes both under ambient conditions and warming treatments. This knowledge will be used to improve Earth system model predictions of these high‐carbon ecosystems from plot to regional scales. Key Points: A new CH4 module was integrated into an Earth system model to predict CH4 fluxes in a northern Minnesota peatland The model accurately predicts the seasonal cycle of methane production and net fluxes CH4 substrate and production were the most critical mechanisms regulating temporal patterns of CH4 fluxes